Effect of drug therapy on nerve repair of moderate-severe traumatic brain injury: A network meta-analysis - Li, Mei; Huo, Xianhao; Wang, Yangyang; Li, Wenchao; Xiao, Lifei; Jiang, Zhanfeng; Han, Qian; Su, Dongpo; Chen, Tong; Xia, Hechun (Frontiers in Pharmacology, 2022)
Abstract: Objective: This network meta-analysis aimed to explore the effect of different drugs on mortality and neurological improvement in patients with TBI, and to clarify which drug might be used as a more promising intervention for treating such patients by ranking. Methods: We searched PubMed, Medline, Embase, and Cochrane Library from the establishment of the database to January 31, 2022. Data were extracted from the included studies, and the quality was assessed using the Cochrane risk-of-bias tool. The outcome measures were mortality, the proportion of favorable outcomes and the occurrence of drug treatment-related adverse effects. Results: We included 30 RCTs that included 12 interventions (TXA, EPO, progesterone, progesterone+vitamin D, atorvastatin, beta-blocker therapy, Bradycor, Enoxaparin, Tracoprodi, dexanabinol, selenium, simvastatin). The analysis revealed that these drugs significantly reduced mortality and increased the proportion of patients with favorable outcomes after TBI. In terms of mortality, the order from the lowest to the highest was progesterone+vitamin D, beta-blocker therapy, EPO, simvastatin, Enoxaparin, Bradycor, Tracoprodi, selenium, atorvastatin, TXA, progesterone, dexanabinol, placebo. In terms of the proportion of patients with favorable outcomes, the order from the highest to the lowest was Enoxaparin, progesterone+vitamin D, atorvastatin, simvastatin, Bradycor, EPO, beta-blocker therapy, progesterone, Tracoprodi, TXA, selenium, dexanabinol, placebo. Based on the classification of GOS, this study also analyzed the three aspects of good recovery, moderate and severe disability. It involved 10 interventions and revealed that compared with placebo, a higher proportion of patients had a good recovery and moderate disability after treatment with progesterone+vitamin D, Bradycor, EPO, and progesterone. Meanwhile, the proportion of patients with a severe disability after treatment with progesterone+vitamin D and Bradycor was also low. Conclusions: This study revealed that TXA, EPO, progesterone, progesterone+vitamin D, atorvastatin, beta-blocker therapy, Bradycor, Enoxaparin, Tracoprodi, dexanabinol, selenium, and simvastatin all reduced mortality and increased the proportion of patients with favorable outcomes in TBI. Among these, the progesterone+vitamin D had not only a higher proportion of patients with good recovery and moderate disability but also a lower proportion of patients with severe disability and mortality. However, whether this intervention can be used for clinical promotion still needs further exploration.